Texts of Light and Shadow: Dickens and Lautréamont in Alejandra Pizarnik's Sombra Poems - Beth Zeiss (Studies in 20th & 21st Century Literature, 2006)
In her poetry, the Argentinean Alejandra Pizarnik (1936-72) persistently explores the transformations that the poetic subject undergoes in language. She articulates a cycle wherein the subject's desire to (re)create herself as a presence in language is followed by the desire for death, the absence of the self, when her desire becomes frustrated by language's inadequacies. As yet, the importance of the theme of the fluctuating self in language as developed by Pizarnik in a series of poems protagonized by Sombra, has not been analyzed. The character Sombra appears in six fragment-like poems published posthumously in Textos de Sombra (1982) and written during the last two years of her life. Pizarnik shows the nature of Sombra's being and non-being in language by implementing two techniques—the palimpsestic technique and the psychological structure of the phantasm. The palimpsestic text is the product of a mode of writing in which a "hypertext," is created through the imitation and/or transformation of an original text, a "hypotext," following the terminology of Gérard Genette. Pizarnik uses short passages from Charles Dickens' A Christmas Carol (1843) as hypotexts for the hypertexts of her Sombra poems. She also employs a scene from Les Chants de Maldoror (1866), by the Count of Lautréamont (Isidore Ducasse), as an additional hypotext to the Sombra poems. The dynamic of the present and absent self plays a central role in both the palimpsestic technique and the structure of the phantasm. For this reason the two techniques serve Pizarnik to develop the character of Sombra as a representation of the fluctuating subject in language.
Keywords: poetry; Argentinean poetry; Alejandra Pizarnik; poetic subject; language; identity; self; Textos de Sombra; hypotext; Dickens; A Christmas Carol; Les Chants de Maldoror; Count of Lautréamont (Isidore Ducasse)